The Effect of Training Age of Under-19 Football Players on Some Physiological Variables of the Cardiocirculatory System (Heart Rate - Blood Pressure) - chahrazed, Abdeldjelil; Nouari, Boutobza; Ahmed, Azzam; mehdi, Benyamina Mohammed; Abdelmalek, Gasmi; Abderrahim, Belabed (Journal of Ecohumanism, 2026)
This study aimed to identify the effect of training age on some physiological variables of the cardiovascular system, namely resting heart rate, post-exercise heart rate, and post-recovery heart rate for one minute, as well as systolic and diastolic blood pressure during the same periods, in under-19 football players. The researcher used the descriptive method with correlation and comparison techniques, as it was suitable for the nature of the study. To confirm the problem and its existence, the researcher conducted a pilot study, which showed that players with more training age had a better understanding of heart rate levels and training loads, as evidenced by their heart rate and its variations during training phases, compared to those with less training age. To verify the validity, reliability, and objectivity of the tests and measurements used in the study, the researcher conducted a pilot study on a random sample of 19 players. The results showed that the tests demonstrated a high degree of validity, reliability, and objectivity. In the main study, the researcher used a sample of 98 players under 19 years of age, representing 8 teams from the east, west, central, and southern regions of Skikda province. These players were selected purposively. The researcher relied on physiological measurements and physical tests in the main study. The physiological measurements consisted of measuring heart rate and systolic and diastolic blood pressure at rest, immediately after exertion, and finally after a one-minute recovery period. The results showed that... - Differences exist between under-19 football players according to their training age groups in functional variables (resting heart rate). - Differences exist between under-19 football players according to their training age groups in functional variables (heart rate and systolic blood pressure after exertion). - Differences exist between under-19 football players according to their training age groups in functional variables (diastolic blood pressure after exertion).